Addressing the sneak-path problem in crossbar RRAM devices using memristor-based one Schottky diode-one resistor array - Gül, Fatih (Results in physics, 2019)
Resistive random access memories (RRAMs) are favorable contenders in the race towards future technologies. Moreover, the desirable properties of memristor-based RRAM devices make them very good competitors in this field. The sneak paths problem poses one of the main difficulties in the construction of crossbar memory devices. This problem can be effectively suppressed by applying the 1diode-1resistor (1D1R) design structure. The Schottky diode has many advantages compared to the PN junction diode. The low-power (∼1 µW) ZnO active-layered thin-film (60 nm thick) one Schottky diode-one memristor device fabricated in this study included a top Ag electrode and a bottom Al electrode. The material makeup of the device was confirmed via energy dispersive X-ray spectroscopy (EDAX). The memristive and Schottky diode characteristics of the Ag/ZnO/Al device were resolved by measuring the time-dependent voltage/current. The characteristic pinched hysteresis memristive loops were observed at the first quadrant of the current-voltage plane, whereas the diode curves were seen at the third quadrant. Using the current-voltage curves, the height of the Schottky barrier, ideality factor and threshold voltage of the Schottky diode were found to be 0.68 eV, 3.75 and 0.49 V, respectively. After physical implementation and characterization of the one diode-one memristor device, its anti-crosstalk characteristics were investigated. Taking into account the 10% read margin, the maximum crossbar size was found to be 87.